2018
DOI: 10.1371/journal.pone.0192168
|View full text |Cite
|
Sign up to set email alerts
|

The effects of anxiety and external attentional focus on postural control in patients with Parkinson's disease

Abstract: BackgroundAlthough anxiety is a common non-motor outcome of Parkinson's disease (PD) affecting 40% of patients, little attention has been paid so far to its effects on balance impairment and postural control. Improvement of postural control through focusing on the environment (i.e. external focus) has been reported, but the role of anxiety, as a confounding variable, remains unclear.ObjectivesThis study aimed to investigate the influence of anxiety and attentional focus instruction on the standing postural con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Concerning the scale's reliability, the present study suggested an acceptable internal consistency of the FES, which is in line with previous studies (α= 0.75-0.98) in elder adults [7,[10][11][12][22][23][24][25][26]. Therefore, this scale's items cover all aspects of FOF.…”
Section: Discussionsupporting
confidence: 90%
“…Concerning the scale's reliability, the present study suggested an acceptable internal consistency of the FES, which is in line with previous studies (α= 0.75-0.98) in elder adults [7,[10][11][12][22][23][24][25][26]. Therefore, this scale's items cover all aspects of FOF.…”
Section: Discussionsupporting
confidence: 90%
“…In our results, different explanations could have contributed to no significant changes under dual-task. First, the cognitive task provides an external focus which diverts attention from body sways and reduces conscious control [ 39 ]. Some studies have shown the potential of external focus to reduce postural instability during quiet standing compared to an internal focus in pwPD [ 40 ] and to improve postural instability when pwPD took dopamine medication [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Automaticity could have been enhanced by an external focus of attention, an idea known as the “constrained action hypothesis” (Wulf et al, 2001; Kal et al, 2013), employed for the reduction of cognitive interference in athletic performance. Maintaining an external focus of attention, like a target or an image, has been shown to be an effective strategy in improving postural control in patients with PD (Wulf et al, 2009; Jazaeri et al, 2018), however no data has been reported on the effects of an external focus on dual task or gait performance. In dance practice, the use of metaphors may serve the purpose of directing attention externally to produce a movement through the use of imagery (Guss-West and Wulf, 2016; Lewthwaite and Wulf, 2017).…”
Section: Discussionmentioning
confidence: 99%